Konsep Pendidikan Akidah Akhlak Dalam Pembentukan Karakter Pendidikan Islam Dan Implikasinya Terhadap Generasi Muda - Sumanto, Edi; Noviani, Dwi; Ramona, Putri Deby (CV. ULIL ALBAB CORP, 2024)
Moral belief education has a strategic role in shaping the character of the younger generation within the framework of Islamic education. Aqidah, as the foundation of faith, and morals, as the implementation of Islamic morals and ethics, are the main pillars in the formation of individuals with good moral character. This research aims to examine the concept of moral education and its implementation in the formation of the character of the younger generation, especially in the context of Islamic education. Through a qualitative approach using literature study methods, this research analyzes the role of moral education in forming a personality that is responsible, disciplined and committed to Islamic values. The research results show that moral education not only plays a role in shaping individual character, but also has a significant impact on the social environment, where the younger generation contributes to creating a moral and religious society. Implementing good moral education in schools, families and communities is the key to overcoming the challenges of modernity and moral decadence faced by today's young generation. Thus, the concept of moral education needs to be strengthened to give birth to the next generation who are strong, have integrity and play an active role in the development of Islamic civilization.